2017
DOI: 10.1186/s13568-017-0381-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and molecular characterization of a novel quorum sensing molecule in Bacillus licheniformis

Abstract: Quorum sensing molecules (QSMs) are involved in the regulation of complicated processes helping bacterial populations respond to changes in their cell-density. Although the QS gene cluster (comQXPA) has been identified in the genome sequence of some bacilli, the QS system B. licheniformis has not been investigated in detail, and its QSM (ComX pheromone) has not been identified. Given the importance of this antagonistic bacterium as an industrial workhorse, this study was aimed to elucidate B. licheniformis NCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…ComX pheromones derived from the comQXPA system of B. subtilis regulate genetic competence, surfactin production, and biofilm formation ( Table 1). They are short peptides (4 -13 amino acids) with a conserved, modified Trp residue that is formed upon isoprenylation and cyclization (157,158) (Fig. 2).…”
Section: Ripps As Qs Signalsmentioning
confidence: 99%
“…ComX pheromones derived from the comQXPA system of B. subtilis regulate genetic competence, surfactin production, and biofilm formation ( Table 1). They are short peptides (4 -13 amino acids) with a conserved, modified Trp residue that is formed upon isoprenylation and cyclization (157,158) (Fig. 2).…”
Section: Ripps As Qs Signalsmentioning
confidence: 99%
“…For example, the sequence similarity between B. subtilis and B. licheniformis was only 62%. 32 Sequence analysis revealed that the QS of B. amyloliquefaciens was only 47%, similar to the ComQXPA of M-24. The function of Amy-QXPA has been confirmed successfully in plipastatin monoproducing engineered strain M-24, but whether it could function and regulate the production of plipastatin dynamically in B. subtilis is still unknown.…”
Section: Resultsmentioning
confidence: 93%
“…QS in Bacillus species is mediated by small peptides based on two‐component regulatory systems that control competence, sporulation and the production of certain secondary metabolites in a cell‐density dependent fashion (Sturme et al, 2002; van Gestel et al, 2012). Esmaeilishirazifard et al (2017) detected a novel QS molecule of B . licheniformis NCIMB‐8874 to be a 10‐amino‐acid component of the ComX precursor.…”
Section: Discussionmentioning
confidence: 99%